Piperacillin/Tazobactam Co-Delivery by Micellar Ionic Conjugate Systems Carrying Pharmaceutical Anions and Encapsulated Drug - Katarzyna Niesyto; Aleksy Mazur; Dorota Neugebauer (MDPI AG, 2024)
Previously obtained amphiphilic graft copolymers based on [2-(methacryloyloxy)ethyl]trimethylammonium chloride (TMAMA) ionic liquid were used as the matrices of three types of nanocarriers, i.e., conjugates with ionic piperacillin (PIP) and micelles with tazobactam (TAZ), which represented single systems, and dual systems bearing PIP anions and encapsulated TAZ for co-delivery. The exchange of Cl anions in TMAMA units with PIP ones resulted in a yield of 45.6-72.7 mol.%. The self-assembling properties were confirmed by the critical micelle concentration (CMC), which, after ion exchange, increased significantly (from 0.011-0.020 mg/mL to 0.041-0.073 mg/mL). The amphiphilic properties were beneficial for TAZ encapsulation to reach drug loading contents (DLCs) in the ranges of 37.2-69.5 mol.% and 50.4-80.4 mol.% and to form particles with sizes of 97-319 nm and 24-192 nm in the single and dual systems, respectively. In vitro studies indicated that the ionically conjugated drug (PIP) was released in quantities of 66-81% (7.8-15.0 μg/mL) from single-drug systems and 21-25% (2.6-3.9 μg/mL) from dual-drug systems. The release of encapsulated TAZ was more efficient, achieving 47-98% (7.5-9.0 μg/mL) release from the single systems and 47-69% (9.6-10.4 μg/mL) release from the dual ones. Basic cytotoxicity studies showed non-toxicity of the polymer matrices, while the introduction of the selected drugs induced cytotoxicity against normal human bronchial epithelial cells (BEAS-2B) with the increase in concentration.